INJIL BERPINDAH MEJA - Pratiwi Eunike; Djonny Pabisa; Dilham Dilham (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2026)
This study examines Acts 13:46-47 as a pivotal moment of oikonomic transition within God’s redemptive plan, situating Paul’s declaration in the synagogue of Pisidian Antioch firmly within the framework of Mid-Acts Dispensationalism. Employing a qualitative, library-based research approach, the study integrates Greek linguistic analysis of the terms apōtheisthe, strapheisometha, and ethnē; a historical-narrative investigation into the social context of the Jewish diaspora and the dynamics of the early church; and a dispensational theological interpretation that sharply distinguishes the program of Israel from that of the Church, the Body of Christ. A review of contemporary scholarship demonstrates that many studies emphasize historical continuity between Israel and the church or focus on the narrative and missional dimensions of Paul’s ministry, yet generally fail to recognize the explicit administrative shift embedded in this text. The study concludes that Israel’s rejection and Paul’s declaration, “we turn to the Gentiles,” is not merely a missional response but an inaugural announcement that the divine mandate of the Gospel understood as God’s program has been transferred from Israel to Paul, and through Paul to the nations, as the enactment of the previously hidden oikonomia of grace. Practically, this implies that contemporary evangelism must be rooted in the Gospel of Grace entrusted to Paul, free from kingdom frameworks and Mosaic regulations, and carried out with the awareness that the church now operates within a new divine administration that no longer centers on Israel but on the Church, the Body of Christ, as a new spiritual creation.